PENGARUH VARIASI CaCo3 TERHADAP ARANG AKTIF PADA PROSES PACK CARBURIZING TERHADAP PENINGKATAN KEKERASAN BAJA KARBON RENDAH DITINJAU DARI STRUKTUR MIKRO DAN KEKERASAN - Hafni, Hafni (Jurnal Teknologi dan Vokasi, 2025)
Because of its soft, ductile and easy-to-work nature, steel is widely used as a material in making a product. To obtain hard properties on the surface and remain soft at the core, a surface hardening process is carried out, so that the product can function according to its design objectives. One way to do this surface hardening is with solid carbon media or pack carburizing. To carry out this carburizing process, a furnace is required that is designed to be heat resistant and easy to operate. safe with coal fuel. for the furnace tester that has been designed, testing was carried out on low carbon steel using 1000 grams of activated charcoal carburization media with variations: 200 grams, 100 grams, 66.7 grams of Calcium carbonate (CaCo3) at a heating temperature of 950 0C and a holding time of 4 hours. Then continued with the quenching process. The test results show that the test material with a composition of 1000 grams of activated charcoal with 200 grams of calcium carbonate is better with the addition of carbon elements so that when quenching is carried out, a martensite microstructure is formed.